Implications for epidemiologic research on variation by pesticide in studies of farmers and their families - Acquavella, John F.; Gustin, C.; Alexander, B. H.; Mandel, J. S. (Scandinavian Journal of Work, Environment & Health, 2005)
Epidemiologic studies rely on participants’ recall to classify their exposure to specific pesticides. As exposure classification evolves, an important issue is whether the recall of pesticide application details can be used to derive measures of exposure intensity or cumulative exposure. A preliminary analysis of biomonitoring data for farmers before, during, and after a pesticide application suggests variation for different pesticides in the proportion with detectable urinary concentrations, urinary levels, and patterns of uptake and elimination. These findings, and the limited predictive modeling done to date, suggest that chemical-specific differences need to be considered in exposure classification schemes. An analysis of biomonitoring data for farm spouses and children found few with appreciable changes in the urinary concentration after a pesticide application. These findings point to the need to validate assumptions about exposures in studies of people who are not directly involved in pesticide application.
Keywords: 2; 4-dichlorophenoxyacetic acid; chlorpyrifos; commentary; epidemiologic research; epidemiologic study; exposure assessment; farmer; farmer’s family; glyphosate; pesticide